Impact of Proestrus on Gene Expression in the Medial Preoptic Area of Mice - Vastagh, Csaba; Liposits, Zsolt (Frontiers in Cellular Neuroscience, 2017)
The antero-ventral periventricular zone (AVPV) and medial preoptic area (MPOA) have been recognized as gonadal hormone receptive regions of the rodent brain that - via wiring to gonadotropin-releasing hormone (GnRH) neurons - contribute to orchestration of the preovulatory GnRH surge. We hypothesized that neural genes regulating the induction of GnRH surge show altered expression in proestrus. Therefore, we compared the expression of 48 genes obtained from intact proestrous and metestrous mice, respectively, by quantitative real-time PCR method. Differential expression of 24 genes reached significance (p<0.05). Genes upregulated in proestrus encoded neuropeptides (kisspeptin, galanin, neurotensin, cholecystokinin), hormone receptors (growth hormone secretagogue receptor, u-opioid receptor), gonadal steroid receptors (estrogen receptor alpha, progesterone receptor, androgen receptor), solute carrier family proteins (vesicular glutamate transporter 2, vesicular monoamine transporter 2), proteins of transmitter synthesis (tyrosine hydroxylase) and transmitter receptor subunit (AMPA4), and other proteins (uncoupling protein 2, nuclear receptor related 1 protein). Proestrus evoked a marked downregulation of genes coding for adenosine A2a receptor, vesicular GABA transporter, 4-aminobutyrate aminotransferase, tachykinin precursor 1, neurotensin receptor 3, arginine vasopressin receptor 1A, cannabinoid receptor 1, ephrin receptor A3 and aldehyde dehydrogenase 1 family, member L1. Immunocytochemistry was used to visualize the proteins encoded by Kiss1, Gal, Cck and Th genes in neuronal subsets of the AVPV /MPOA of the proestrous mice. The results indicate that gene expression of the AVPV/MPOA is significantly modified at late proestrus including genes that code for neuropeptides, gonadal steroid hormone receptors and synaptic vesicle transporters. These events support cellular and neuronal network requirements of the positive estradiol feedback action and contribute to preparation of the GnRH neuron system for the pre-ovulatory surge release.